“Can We Talk?”: Boundary Crossing and Sexual Misconduct in Seminary Teaching - Ashby, Homer U. (Teaching theology and religion, 2002)
This article explores a variety of personal and professional boundary issues encountered by seminary faculty. The authors contend that boundary crossing is inevitable in contemporary theological education, which is structured such that professors engage in multiple roles with students as they attend to the education of the whole person. Guidelines are reviewed for minimizing risk to students and professors. Topics include life as a community member, student-faculty friendship, and romantic relationships. Attention to work/life balance is seen as critical to the prevention of misconduct. The article ends with a call for continued conversation as well as institutional accountability and change.